2015
DOI: 10.1056/nejmoa1406192
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked TEX11 Mutations, Meiotic Arrest, and Azoospermia in Infertile Men

Abstract: BACKGROUND The genetic basis of nonobstructive azoospermia is unknown in the majority of infertile men. METHODS We performed array comparative genomic hybridization testing in blood samples obtained from 15 patients with azoospermia, and we performed mutation screening by means of direct Sanger sequencing of the testis-expressed 11 gene (TEX11) open reading frame in blood and semen samples obtained from 289 patients with azoospermia and 384 controls. RESULTS We identified a 99-kb hemizygous loss on chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
223
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(244 citation statements)
references
References 40 publications
8
223
2
4
Order By: Relevance
“…Mutations in the X-linked androgen receptor (AR) gene have been shown to be associated with disorders in male sexual differentiation and development (9). More recently, mutations in the X-linked gene, TEX11, have been identified as a cause of meiotic arrest and azoospermia (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the X-linked androgen receptor (AR) gene have been shown to be associated with disorders in male sexual differentiation and development (9). More recently, mutations in the X-linked gene, TEX11, have been identified as a cause of meiotic arrest and azoospermia (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…14) have made a compelling case. Recently, hemizygous deletions of the TEX11 gene, presumably catalyzed by unequal recombination between repetitive elements in the locus, have been linked to maturation arrest and infertility in azoospermic men (15).…”
mentioning
confidence: 99%
“…It was reported that male Tex11 ‐knockout mice showed infertility, with azoospermia that was caused by meiotic arrest 107. In 2015, a whole‐genome array comparative genomic hybridization screening study that involved 15 patients with azoospermia was conducted 108. A recurrent 99 kb TEX11 intragenic deletion (Xq13.2) was identified in two unrelated patients.…”
Section: Culprit Genes That Have Been Identified In the X Chromosomementioning
confidence: 99%
“…This loss, which was identical in both the patients with azoospermia, predicts a deletion of 79 amino acids within the SPO22 region. Mutation screening was performed by means of direct Sanger sequencing of the TEX11 open reading frame in the blood and semen samples that had been obtained from 289 patients with azoospermia and from 384 controls 108. This showed five novel TEX11 mutations: three splicing mutations and two missense mutations.…”
Section: Culprit Genes That Have Been Identified In the X Chromosomementioning
confidence: 99%
See 1 more Smart Citation